THE INFLUENCE OF SOCIAL MEDIA (TIKTOK) TOWARDS INTEREST IN ENGLISH LEARNING AT TEN GRADE OF SMA YADIKA 13 TAMBUN - Fadia Salsabilla Putri (Samudra Publisher, 2024)
The method that information technology uses today has a big influence on many aspects of things in life, including education. TikTok has become one of the most well-liked social networking sites, especially among younger people. TikTok is a social media application that is increasingly popular among internet users. This application allows users to create and share short videos lasting 15 to 60 seconds (Mavellyno, 2023). Apart from being for entertainment, TikTok can also be a tool for disseminating information and learning. In the context of English learning, TikTok offers interesting opportunities to be integrated as a learning medium. This research will compare the effectiveness of using TikTok in increasing interest in learning English. This research aims to determine whether there is a relationship between the use of social media (TikTok) and high school students' interest in learning and how strong the relationship between them is. This research was conducted at SMAS YADIKA 13 TAMBUN by filling out a questionnaire filled in by grade 10 students. The data collection results obtained a calculated value of 0.693 and at a significance level of 5% a value of 0.230 was obtained. The results indicate that students' enthusiasm for learning is significantly impacted by their use of TikToK social media. The study's findings indicate that using social media can increase students' motivation in learning English.